2022
DOI: 10.1007/s12040-022-01811-6
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy)

Abstract: Sandy beaches are the result of a dynamic interaction among physical conditions, biological processes and the anthropic impact (essentially linked to the natural resource direct or indirect exploitation). Monitoring the health state of coastal areas is a fundamental tool for land-use management. Moreover, integrated sedimentological studies with multidisciplinary methodologies are increasingly needed. This study aims to monitor the evolution of Torre Guaceto beach (Brindisi) over different seasons. The study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Wave directions are mainly between 330 • (16.79%) and 120 • (15.36%). It is also observed that the highest frequency of appearance (22.15%) and the highest significant wave heights (Hs between 3 m and 4 m) derive from the 0 • direction [94].…”
Section: Study Areamentioning
confidence: 87%
“…Wave directions are mainly between 330 • (16.79%) and 120 • (15.36%). It is also observed that the highest frequency of appearance (22.15%) and the highest significant wave heights (Hs between 3 m and 4 m) derive from the 0 • direction [94].…”
Section: Study Areamentioning
confidence: 87%
“…The current coastal morphology of the Torre Guaceto site has been gradually shaped by several events of marine transgression/regression cycles that occurred during the Middle-Late Pleistocene period [25]. The Adriatic Apulian beaches are affected by the sediment supplies of the Ofanto river, which are subsequently redistributed by the predominant NW-SE longshore current [26]. This coastal sector, which is a microtidal environment with a narrow foreshore area, is influenced by winds that blow from the NNW and ESE directions and strongly influence wave patterns.…”
Section: Study Areamentioning
confidence: 99%
“…Hydrodynamic flow is simulated with the FLOW module, which solves the unsteady shallow water equations in two (depth-averaged) or three dimensions (Deltares, 2018a). Many studies have shown that Delft3D has been shown to be robust and accurate in predicting nearshore flows (Chu, 2019;Seiler et al, 2020;Lapietra et al, 2022). D-WAQ PART is a random walk particle tracking model suitable for research application in a moderate scale range (200-15000m).…”
Section: Numerical Simulationmentioning
confidence: 99%